Effects of modified tall oil on growth and body composition in adult ovariectomized rats - O'Quinn, P.R.; Koo, S.I.; Noh, S.K.; Nelssen, Jim L.; Goodband, Robert D.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A trial was conducted to evaluate the effects of modified tall oil (MTO) on growth and body composition of adult ovariectomized rats. This trial was targeted as a model for postmenopausal women; thus, only data applicable to swine production are presented herein. Feeding MTO decreased adiposity, increased concentrations of certain lipids in tissues, increased vitamin E (octocopherol) levels in the adipose, and increased actual lean content. These data lend support to the carcass leanness and meat quality improvements routinely seen in swine from feeding MTO.
Keywords: Swine; Rats; Modified tall oil; Vitamin E; Conjugated linoleic acid